Global TESOL for the 21st century : c - Rose, H.; Rose, H.; Syrbe, Mona; Montakantiwong, Anuxgaya (UK : c)
"This book explores the impact of the spread of English on language teaching and learning. It provides a framework for change in the way English is taught to better reflect global realities and to embrace current research. The book is essential reading for postgraduate researchers, teachers and teacher trainers in TESOL"-- Provided by publisher.
includes bibliographical references and index.